The expression and functional role of proline-rich 15 in non-small cell lung cancer - Yong Ji; Han Zhang; Fei-long Gong; Jia-long Liang; Sheng-fei Wang; Yong-hua Sang; Ming-feng Zheng (Cell Death and Disease)
Abstract Proline-rich 15 (PRR15) is a protein primarily known for its role in placental development. This study investigates the expression, functional significance, and underlying mechanisms of PRR15 in non-small cell lung cancer (NSCLC). Our findings demonstrate significantly elevated PRR15 expression in NSCLC tissues compared to normal lung parenchyma, with higher expression correlating with adverse clinical outcomes. Single-cell RNA sequencing confirmed PRR15 overexpression within the malignant tumor cell population. PRR15 expression was elevated in NSCLC tissues from locally treated patients and in a panel of primary and established NSCLC cells. PRR15 depletion using shRNA or CRISPR/Cas9-mediated knockout significantly suppressed proliferation and migration, while promoting apoptosis in various NSCLC cells. Conversely, ectopic PRR15 overexpression using a lentiviral construct enhanced cell proliferation and migration. Mechanistic investigations implicated PRR15 in the activation of the Akt-mTOR signaling pathway. Inhibition of PRR15 expression via shRNA or CRISPR/Cas9-mediated knockout resulted in decreased Akt and S6K phosphorylation, while PRR15 overexpression led to augmented Akt-S6K signaling in primary human NSCLC cells. In vivo studies using xenograft models further validated the oncogenic role of PRR15, demonstrating that PRR15 knockdown suppressed tumor growth and attenuated Akt-mTOR activation. These findings collectively highlight the potential of PRR15 as a novel oncogenic driver and therapeutic target in NSCLC.